Centella Asiatica (GOTU KOLA) TREATMENT ATTENUATES PRO-INFLAMMATORY MEDIATORS IN LIVER OF RATS WITH ELECTRICAL FOOT SHOCK STRESS MODEL - Sari, Dwi Cahyani Ratna; Setyaningsih, Wiwit Ananda Wahyu; Mainichi, Rizky Nur; Dara, Gita Mumtarin; Kemalasari, Ratih; Romi, Muhammad Mansyur; Ar Rochmah, Mawaddah; Arfian, Nur (African Journal of Traditional, Complementary and Alternative Medicines, 2023)
Background: Stress induces secretion of cathecolamines and glucocorticoids, which may produce liver injury. Followed by the production of inflammatory mediators, it causes apoptosis. Centella asiatica (CeA) has anti-inflammatory and hepatoprotective effects. The present study aims to determine the role of CeA in the attenuation of liver pro-inflammatory mediator expression in rats with electrical foot shock stress model. Materials and Methods: Twenty-four Sprague-Dawley rats were randomized into four groups consisted of six rats each: (1) Control group, (2) CeA-treated group, (3) Stress group, and (4) CeA + stress group. Reverse transcriptase PCR of inflammatory and apoptosis markers as well as Real-Time PCR of β2-adrenergic receptor were performed from liver tissues. Results: Electrical foot shock stress induced up-regulation of NFκB and TNF-α mRNA expressions as pro-inflammatory mediators, compared to control group. This alteration was followed by up-regulation of BAX and β2-adrenergic receptor, as well as the down-regulation of BCl2 compared to control. CeA treatment prevented enhancement of NFκB, TNF-α, TLR-4 and β-adrenergic receptor mRNA expressions, which was followed by down-regulation of BAX and up-regulation of BCl-2, compared to stress group. Conclusion: CeA prevents secretion of pro-inflammatory chemokines and cytokines as well as apoptotic markers in liver cells through the activation of β2-adrenergic receptor.